The Paradigm of Thinking of Pesantren Figure (Prof. KH. Tolhah Hasan) and its Impact on Islamic Education - Sholihah, Ni'matus; M. Yunus Abu Bakar (Jurnal Kependidikan Islam, 2024)
Islamic education in Indonesia must continue to always develop to keep up with the times so as not to be left behind. The development of Islamic education was influenced by several thoughts from educational scientists and clerics in Indonesia, one of whom was Prof. KH. Tholha Hasan). In his view, education is not only limited to Islamic labels or Islamic institutions, such as Islamic boarding schools or madrasas, nor is it limited to learning Islamic religious sciences such as monotheism, hadith interpretation, fiqh, and tasawuf. However, Islamic education includes all activities, vision, mission, institutions, curriculum, methodology, teaching and learning processes, educational human resources, an educational environment that is inspired and based on Islamic teachings and values. Muhammad Tholha Hasan's thoughts on Islamic education belong to the construction of thought that has been put forward, namely ethical humanism or education that humanizes himself and other humans, all of which is carried out with a framework of moral foundations so as to give birth to a world colored by civilization